Metode Penetapan Fatwa Dalam Membangun Perdamaian Perspektif Imam Ali goma (Studi Analisis Fiqh Tashabbuh Dengan Non Muslim): Metode Fatwa; Perdamaian; Imam Ali gomaa; Tasyabbuh - Muhammad Nuruddien Nuruddien; Mahmoud Ismaeil Mohamed Mashal (Center for Research and Development of Religious Literature and Heritage, 2023)
A fatwa is a matter of great significance in Islam. The issuer of a fatwa represents the role of Prophet Muhammad (peace be upon him) in continuing his prophetic mission by providing explanations in accordance with the will of God. Therefore, issuing a fatwa is not an easy task, and it is not appropriate for everyone to assume the ability to issue fatwas without undergoing a thorough thought process. It is not permissible for someone to issue a fatwa to the general public unless they possess expertise in the fields of Islamic sciences and have a strong command of fiqh (jurisprudence) and usul al-fiqh (principles of jurisprudence), along with the appropriate methods and objectives (maqasid). This raises the question of how to formulate a method for issuing fatwas from the perspective of Imam Ali Gomaa and why scholars pay great attention to the formation of fatwa methods This research falls under normative research using the literature method, which involves reviewing texts from classical and contemporary fiqh books, as well as fatwa rulings. The findings of this study indicate that the process of issuing a fatwa should go through four stages: al-tashwir (defining the issue), al-takyif (exploring the details), explaining the legal ruling, and making the final fatwa decision The issuer of a fatwa must adhere firmly to the fatwa method, which includes understanding the texts and the reality of society, and knowing how to connect the text with existing societal traditions. They should prioritize issuing fatwas that facilitate and bring joy to society, maintaining moderation and balance in their fatwas, and avoiding haste in addressing contemporary issues. Not all acts of resemblance (tashabbuh) with non-Muslims are considered forbidden (haram). There are acts of resemblance that are indeed judged to be outside the boundaries of Islam, while others are merely disliked (makruh), not recommended, forbidden (haram), permissible (mubah), or even commendable. The observance of the Gregorian New Year is permissible since it does not entail elements of resemblance (tashabbuh), provided that it is not accompanied by religiously prohibited behaviors. The permissibly of celebrating new year is in line with the condition of Madura teenagers. Although, the Madura scholars alliance (AUMA) forbids it because it is considered to resemblance (Tashabbuh) with non muslims.